Pulmonary fibrosis associated with nabumetone. Issue 793 (November 1991) - Morice, A.; Atherton, A.; Gleeson, F.; Stewart, S.
Abstract : A patient is described who developed a rapid onset of pulmonary fibrosis following treatment with a new non-steroidal anti-inflammatory drug, nabumetone. Resolution of symptoms, physical signs and radiographic changes followed drug withdrawal and steroid therapy.